THE CONCEPT OF TRAUMATIC CHILDBIRTH AND PSYCHOPATHOLOGICAL CONSEQUENCES - Milosavljevic Markovic, Maja; Radonjic, Nevena; Miljevic, Cedo; Vukovic, Olivera (Medical Research, 2026)
Childbirth is expected to be a predictable and positive experience in a woman's life. Nevertheless, traumatic experiences related to childbirth have been described for years, which in the most severe cases can result in the onset of postpartum post-traumatic stress disorder. According to current evidence, about 4.7% of women after delivery will meet the criteria for Childbirth-Related Post-Traumatic Stress Disorder (CB-PTSD) diagnosis. Unfortunately, little is known about the aspects of traumatic childbirth, the risk factors for the occurrence of this disorder are insufficiently known, and if it progresses to a clinical diagnosis of post-traumatic stress disorder, it is rarely diagnosed and even less often treated. Viewing childbirth as a traumatic experience can have numerous consequences in the form of avoiding subsequent pregnancies, sexual relations or gynecological examinations, avoiding obligations regarding the newborn, breastfeeding, making attachment with the baby difficult, and the relationship between partners can become dysfunctional. Given this, it is extremely important to increase professional and general awareness of this mental disorder, getting to know the risk factors for its occurrence and possibilities for its diagnosis and treatment.
Keywords: traumatic delivery, postpartum posttraumatic stress disorder